Prognostic nutritional index is useful for predicting the prognosis of patients with infective endocarditis undergoing surgery: a retrospective study - Abulimiti, Kadeyanmu; Liu, Zheng; Dawuti, Maierhaba; Waili, Alapati; Shi, Lin; Zhang, Weimin (Frontiers in Nutrition, 2025)
ObjectiveTo investigate the predictive efficacy of preoperative prognostic nutritional index (PNI) for clinical outcomes in patients with infective endocarditis (IE) undergoing surgical treatment.MethodsA retrospective analysis was conducted on 373 IE patients who underwent cardiac valve surgery in the Department of Cardiac Surgery, the First Affiliated Hospital of Xinjiang Medical University from January 1, 2009 to December 31, 2023. According to the preoperative PNI scores, patients were divided into the malnourished group (132 cases) and the well-nourished group (241 cases). Univariate and multivariate Logistic regression analyses were used to explore the association between preoperative PNI and postoperative in-hospital mortality as well as 1-year all-cause mortality.ResultsThis study analyzed 373 patients who underwent surgery for IE to assess the impact of preoperative nutritional status on prognosis. According to the preoperative PNI, 35.4% (132 patients) were malnourished. Compared with the well-nourished group, the malnourished group had a lower body mass index (BMI) (20.94 vs. 22.84, P < 0.001) and a higher proportion of NYHA class III–IV heart function (53.79% vs. 31.95%, P < 0.001). Multivariate analysis revealed that a lower preoperative PNI score (OR = 0.91, 95% CI: 0.83∼0.99, P = 0.033) and longer cardiopulmonary bypass (CPB) time (per 10-min increase: OR = 1.15, 95% CI: 1.07∼1.24, P < 0.001) were independent risk factors for postoperative in-hospital mortality. Similarly, preoperative PNI score (OR = 0.95, 95% CI: 0.90–0.99, P = 0.040) and CPB time (per 10-min increase: OR = 1.10, 95% CI: 1.04–1.16, P = 0.001) were also independent predictors of 1-year all-cause mortality. ROC curve analysis showed that the predictive ability of PNI for postoperative in-hospital mortality (AUC = 0.74) was better than that for 1-year mortality (AUC = 0.61).ConclusionPreoperative PNI score can effectively reflect the nutritional-immune status of patients with IE. It is not only an independent risk factor for predicting postoperative in-hospital mortality and 1-year all-cause mortality, but also has certain short-term predictive ability and identification value for long-term outcomes, which can provide a reference for clinical early identification of high-risk patients and formulation of nutritional intervention strategies.